2021
DOI: 10.3389/fendo.2021.637384
|View full text |Cite
|
Sign up to set email alerts
|

Roles of miR-10a-5p and miR-103a-3p, Regulators of BDNF Expression in Follicular Fluid, in the Outcomes of IVF-ET

Abstract: Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, plays critical roles in the physiological process of oocyte mature and IVF outcomes of patients with infertility. However, the regulation of BDNF expression in the microenvironment surrounding the oocyte is still unknown. We initially predicted some microRNA (miRNA) candidates targeting bdnf with a series of bioinformatics analysis tools to determine the underlying regulatory mechanisms of BDNF, particularly the effect of miRNAs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…To provide insights in the regulation of proBDNF synthesis, we measured diverse urinary factors and microRNAs known to control the translation of proBDNF mRNA ( Table 5 ). MiR-26b-5p, miR-26a-5p, miR-10a-5p, and miR-103a-3p that bind the 3′UTR sequence of proBDNF mRNA were not expressed differently between control and OAB patients [ 25 , 26 ]. Levels of other miRNAs (miR-15b-5p, miR-142-3p and miR-103a-3p) that control proBDNF expression through downstream or upstream pathways were also not different [ 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide insights in the regulation of proBDNF synthesis, we measured diverse urinary factors and microRNAs known to control the translation of proBDNF mRNA ( Table 5 ). MiR-26b-5p, miR-26a-5p, miR-10a-5p, and miR-103a-3p that bind the 3′UTR sequence of proBDNF mRNA were not expressed differently between control and OAB patients [ 25 , 26 ]. Levels of other miRNAs (miR-15b-5p, miR-142-3p and miR-103a-3p) that control proBDNF expression through downstream or upstream pathways were also not different [ 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-26b-5p, miR-26a-5p, miR-10a-5p, and miR-103a-3p that bind the 3′UTR sequence of proBDNF mRNA were not expressed differently between control and OAB patients [ 25 , 26 ]. Levels of other miRNAs (miR-15b-5p, miR-142-3p and miR-103a-3p) that control proBDNF expression through downstream or upstream pathways were also not different [ 25 , 27 , 28 ]. On the other hand, concentration of miR-491-5p, which negatively controls MMP-9 expression, was significantly decreased in the OAB group: 0.122 (Q1, Q3: 0.0221, 0.392) vs. 0.533 (Q1,Q3: 0.302, 1.643) in the control group, p < 0.05 ( Figure 1 c) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the top 20 highly enriched miRNAs found within hMSCs are known to upregulate BDNF expression ( Kodali et al, 2023 ). Instead, several miRNAs enriched in hMSC-EVs can decrease BDNF concentration, which includes miR-26b ( Caputo et al, 2011 ), miR-10a-5p ( Zhang Q et al, 2021 ), miR-10b-5p ( Müller, 2014 ), and miR-30a-3p ( Mellios et al, 2008 ). Still, the combined effects of the miRNA and protein cargo of hMSC-EVs improving BDNF-ERK-CREB signaling after TBI cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al found that upregulation of miR-103a-3p promoted chondrocyte proliferation of human osteoarthritis (OA) and inhibited cell apoptosis and in ammatory responses [21]. Zhang et al reported that miR-103a-3p exerted negative in uences on the maturation of oocytes by regulating brain-derived neurotrophic factor (BDNF) expression in human follicular uid [22]. These studies all con rm that miR-103a-3p and miR-214 play an important regulatory role in cell apoptosis and oxidative stress, consistent with the data in the current study.…”
Section: Discussionmentioning
confidence: 99%